2022
DOI: 10.1186/s12870-022-03792-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide screening of lectin putative genes from Sorghum bicolor L., distribution in QTLs and a probable implications of lectins in abiotic stress tolerance

Abstract: Background Sorghum bicolor is one of the most important crops worldwide with the potential to provide resilience when other economic staples might fail against the continuous environmental changes. Many physiological, developmental and tolerance traits in plants are either controlled or influenced by lectins; carbohydrate binding proteins. Hence, we aimed at providing a comprehensive in silico account on sorghum’s lectins and study their possible implication on various desired agronomical trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 88 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…Tolerance to abiotic stress is intricate and often controlled by a large number of quantitative trait loci (Mwamahonje et al, 2021;Osman et al, 2022). The generation of superior lines with enhanced resilience to abiotic stress using molecular breeding procedures has a limited track record of success (Tonapi et al, 2020).…”
Section: Abiotic Stress Tolerancementioning
confidence: 99%
“…Tolerance to abiotic stress is intricate and often controlled by a large number of quantitative trait loci (Mwamahonje et al, 2021;Osman et al, 2022). The generation of superior lines with enhanced resilience to abiotic stress using molecular breeding procedures has a limited track record of success (Tonapi et al, 2020).…”
Section: Abiotic Stress Tolerancementioning
confidence: 99%
“…Recently, a large set of unconventionally secreted lectins with a potential function in abiotic stress signalling, was identified in sorghum ( Sorghum bicolor ), based on the identification of quantitative trait loci known to be important for abiotic stress signalling. These analyses revealed a potential association with cold and drought stress signalling ( Osman et al, 2022 ).…”
Section: Secreted Plant Lectins and Stress Signallingmentioning
confidence: 99%
“…Sorghum (Sorghum bicolor (L.) Moench) is the fifth most important cereal crop, providing human foods, animal feeds, and bioenergy. Notably, sorghum exhibits exceptional tolerance to abiotic stresses, such as salinity and drought, making it an ideal crop in the face of changing climate conditions ( Osman et al., 2022 ). In this study, by comprehensive analysis of cellular components, we found that Arthrospira is capable of synthesizing compatible solutes, among them GG and Tre, and confirmed their positive effect in plant salt tolerance.…”
Section: Introductionmentioning
confidence: 99%